User Perceptions of C-Access App: A Study of Passenger Experience in Jakarta KRL Commuter Line - Amiroh Allabibah; Sylvia A Roennfeld; Muhammad Hafiz Nurul Haqqi (Universitas Multimedia Nusantara, 2024)
The C-Access app by PT Kereta Commuter Indonesia is a popular tool among public transportation users in Jakarta, providing real-time schedules, fare calculations, and route information. Despite its functionality, user satisfaction has been affected by technical issues, particularly schedule inaccuracies, which have led to overcrowding and dissatisfaction during peak hours. This qualitative study explores the app's reputation by focusing on four key elements: credibility, reliability, trustworthiness, and responsibility. Findings reveal that while the app is generally credible and appreciated for aiding commuting decisions, reliability issues such as slow updates and occasional technical glitches pose challenges. Users generally trust the app, but trust decreases with inconsistencies in schedule information, leading to discomfort. Moreover, the study highlights PT KCI's ongoing efforts to address these issues and improve user experience, although faster response times are needed. The C-Access app, backed by PT KAI's reputation as a state-owned enterprise, retains strong credibility but requires enhanced operational reliability to maintain user trust and satisfaction. Addressing these challenges could strengthen the app's reputation and ensure sustained customer loyalty.